Pengaruh Return On Assets, Current Ratio, Debt To Equity Ratio Terhadap Harga Saham Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Saskia Anastasya Dwi Putri; Alamsjah, Alamsjah; A.Tenri Syahriani (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on stock prices during the period 2019–2023. The research method employed a quantitative approach with multiple linear regression analysis. The sample was selected using purposive sampling technique. The results of the study indicate that, partially, ROA has a significant influence on stock prices, while CR and DER do not show any significant effect. These findings suggest that among the financial ratios examined, only ROA serves as a relevant indicator that influences investor decisions, whereas CR and DER do not have a substantial impact on stock price fluctuations.